Estimate of false-positive breast cancer diagnoses from accuracy studies: a systematic review. Issue 4 (10th January 2017) - Segnan, Nereo; Minozzi, Silvia; Ponti, Antonio; Bellisario, Cristina; Balduzzi, Sara; González-Lorenzo, Marien; Gianola, Silvia; Armaroli, Paola
Abstract : Background: False-positive histological diagnoses have the same consequences of overdiagnosis in terms of unnecessary treatment. The aim of this systematic review is to assess their frequency at needle core biopsy (CB) and/or surgical excision of the breast. Methods: PubMed, Embase, Cochrane Library were systematically searched up to 30 October 2015. Eligibility criteria: cross-sectional studies assessing diagnostic accuracy of CB compared with surgical excision; studies assessing reproducibility of pathologists reading the same slides. Outcomes: false-positive rates; Misclassification of Benign as Malignant (MBM) histological diagnosis; K statistic. Independent reviewers extracted data and assessed quality using an adapted QUADAS-2 tool. Results: Sixteen studies assessed CB false-positive rates. In 10 studies (41 989 screen-detected lesions), the range of false-positive rates was 0%–7.1%. Twenty-seven studies assessed pathologists' reproducibility. Studies with consecutive, random or stratified samples of all the specimens: at CB the MBM range was 0.25%–2.4% (K values 0.83–0.98); at surgical excision, it was 0.67%–1.2% (K values 0.86–0.94). Studies with enriched samples: the MBM range was 1.4%–6.2% (K values 0.57–0.86). Studies of cases selected for second opinion: the MBM range was 0.29%–12.2% (K values 0.48 and 0.50). Conclusions: High heterogeneity of the included studies precluded formal pooling estimates. When considering studies of higher sample size or methodological quality, false-positive rates and MBM are around 1%. The impact of false-positive histological diagnoses of breast cancer on unnecessary treatment, as well as that of overdiagnosis, is not negligible and is of importance in clinical practice.